COPPER - NICKEL ALLOYS FOR MARINE AQUA CULTURAL ENGINEERING - RAVINDRAN, K (Fishery Technology, 2017)
Engineering developments, problems of marine corrosion, fouling and practical innovative applications of copper-nickel alloys in comparison with other materials for marine aquacultural engineering are presented. Coefficient of drag and hydrodynamic force acting on nylon and polyethylene net enclosures have shown a four-fold increase of force in four months at the Cochin Harbour due to fouling. Corrosion behaviour of copper-nickel and other copper base alloys are also presented. Effects of copper additions to culture water are reviewed.